UPAYA PENINGKATAN KEMAMPUAN BACA TULIS AL-QUR’AN BAGI PESERTA DIDIK DENGAN METODE TALAQQI - Zainal Abidin; Moh. Mahfud; Irwan Setia Budi (CV. Jendela Gagasan, 2025)
The ability to read and write the Qur’an is very important for Muslims, because the Qur’an is a way of life for Muslims. Therefore learning about reading and writing the Qur’an is taught from an early age. But there are still many who have not been able to read and write the Qur’an due to several factors. For this reason, this article will discuss how the author provides guidance to students regarding the ability to read and write the Qur’an that students can read and write the Qur’an fluently and well. In this coaching the author does it gradually but in a very short period of time. In this very short period of time, it is impossible for studets to be able to immediately be fluent and good at reading and writing the Qur’an. Therefore, the author made an innovation so that students can read and write the Qur’an fluently and well. Namely the author uses the Talaqqi method in order to attract students to read and write the Qur’an and this method can help them in accelerating their fluency in reading and writing the Qur’an.